Strain and rotation rate patterns of mainland Greece from continuous GPS data and comparison between seismic and geodetic moment release. Issue 5 (26th May 2015) - Chousianitis, Konstantinos; Ganas, Athanassios; Evangelidis, Christos P.
Abstract We processed data from ~100 continuous GPS stations to provide new insights into the crustal motion and deformation of central and western Greece. We used the derived velocity field to evaluate two‐dimensional strain and rotation rate tensors, and we mapped the dilatation and maximum shear strain rates. In central Peloponnese and Epirus, we documented a 90° switch in the extension direction, which can be explained on the basis of the plate boundary configuration. Evidence for an extended deformation pattern in central Greece was found. Additionally, we detected two pairs of shear belts, one in Akarnania‐NW Peloponnese and one in North Aegean. We delineated two rotational domains that dominate the present‐day pattern. Moreover, we saw no geodetic evidence for North Anatolian Fault growth toward central Greece. We translated the geodetic strain rates into rates of seismic moment release and compared them with earthquake catalog‐based moment rates. In the central Ionian Sea, the geodetic strain is completely released seismically, which is indicative of a fully coupled seismogenic zone. However, for most of the study area, the geodesy‐based moment rates are at least 2 times higher than the earthquake‐based rates. We attribute this mainly to earthquake catalog representativity over the long‐term situation. However, for the Gulf of Corinth, it is unrealistic to associate the high ratio of geodetic to seismic moment rates only to incompleteness of the earthquake catalog; instead, long‐term aseismic deformation must be an important mechanism accommodating a considerable portion of the strain budget, especially at its western part.